The Upper Paleolithic and Epipaleolithic of Sefunim Cave, Israel. (10th January 2018) - Shimelmitz, Ron; Friesem, David E.; Clark, Jamie L.; Groman-Yaroslavski, Iris; Weissbrod, Lior; Porat, Naomi; Kandel, Andrew W.
Abstract: Sefunim Cave, Mount Carmel, Israel was previously excavated in the 1960s and is one of the main sites known for the occurrence of the cultural entity termed the Levantine Aurignacian. Renewed excavations at Sefunim Cave provide new insights into the Late Pleistocene occupations of the site and reveal a rich Epipaleolithic layer, in addition to the previously recorded Middle to Upper Paleolithic sequence. The recent work helps us re-evaluate the record of cultural and environmental shifts within the Upper Paleolithic and early Epipaleolithic sequence and places the results of earlier excavations in a higher resolution context in terms of human-environment relationships. The current work reports the first radiometric dating results from the Upper Paleolithic layers at this key site. In addition, we provide a preliminary description of finds collected during the new campaigns. The finds encompass both the material culture and environmental setting of Sefunim, and include investigations of micromorphology, lithics, use-wear, fauna, microfauna, ocher and shells. Important new findings include the identification of rich symbolic activity at the site. In the Levantine Aurignacian assemblage it is represented primarily by the presence of numerous shell ornaments, a trend which parallels Upper Paleolithic sites of the northern Levant. Other manifestations of symbolic activity are represented by ocher exploitation throughout the sequence and a unique engraved artifact from the Epipaleolithic.